Islam Sebagai Objek Studi Pendidikan Agama Islam - Mahmudah, Mila (Tarunaedu: Journal of Education and Learning, 2025)
Abstract Islam as a study target and research object literally is a study and research on matters related to Islam, discussing systematic and integrated studies to know, understand, and analyze in depth matters related to Islam. Islam in the object of Islamic Religious Education is an effort to study Islam by applying scientific methods, especially in the context of social science. The object of Islamic Religious Education is usually termed Islam at three levels, namely Islam as revelation, Islam as understanding or thought, and Islam as practice in Society. This study uses the Literature review method to study Islam as a study of the field of Islamic studies (Dirosah Islamiyah). Where in this discussion it was concluded that: sialam as an object of study of Islamic Religious Education is a conscious and systematic effort to know and understand and discuss in depth the ins and outs or matters related to Islam, both related to teachings, history and practices of its implementation in real life.